Maintaining Standards and Increasing Accessibility of the Certified Performance Technologist Credential. Issue 8 (19th September 2013) - Snyder, Dawn M.; Moore, Andrea; Rasile, Pat
Abstract The Certification and Accreditation Governance Committee of the International Society for Performance Improvement (ISPI) ensures that certification standards reflect current research and best practice. This article discusses changes to the Certified Performance Technologist Standards based on the 2012 Certified Performance Technology Validation Study and other inputs. It describes the process used to achieve consensus and make the changes to keep the standards current and relevant. It also describes how the language of the standards was changed to make the standards accessible to all of ISPI's audiences, including ISPI's growing international audience.